Pengaruh Pembinaan dan Pengawasan Internal Organisasi Terhadap Semangat Kerja Pegawai: (Studi pada Kantor Penyelenggara Pelabuhan Pangandaran) - Mastur Mastur; Aini Kusniawati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research is motivated by the low performance of employees which is suspected to be caused by the lack of intensive coaching by the leadership and the lack of effective internal supervision of the organization. The purpose of this study is to determine how coaching affects employee morale, how internal organizational supervision affects employee morale, and how coaching and internal organizational supervision together affect employee morale. The method used in this study uses a quantitative descriptive method. To analyze it, correlation and multiple regression statistical test data analysis was used using SPSS version 22.00. The results of the study obtained provide the conclusion that coaching has a positive and significant effect on employee morale, internal organizational supervision has a positive and significant effect on employee morale, and coaching and internal organizational supervision together have a positive and significant effect on employee morale.